2013
DOI: 10.4103/1477-3163.112268
|View full text |Cite
|
Sign up to set email alerts
|

Digitoxin induces apoptosis in cancer cells by inhibiting nuclear factor of activated T-cells-driven c-MYC expression

Abstract: Background:Cardiac glycosides such as digitoxin have been shown to directly cause apoptotic death of cancer cells both in vitro, and in vivo. However, the mechanism connecting cardiac glycoside action to apoptosis is not known. It has been reported that compounds resembling digitoxin are able to reduce c-MYC expression. Furthermore, it has been previously shown that the transcription of c-MYC depends on nuclear factor of activated T-cells (NFAT) binding sites in the c-MYC promoter. We have therefore hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 47 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…Up to date, most of the NFAT inhibitors have been developed to nonspecifically inhibit all calcineurin-responsive NFAT isoforms no matter whether they exert their roles as an oncogene or a tumor suppressor, resulting in suboptimal efficacy against human cancer and unexpected side effects on human immune system. Several NFAT inhibitors that target either oncogenic NFAT isoforms, such as helenalin [ 51 ] and zoledronic acid [ 52 ], or NFAT-DNA binding, such as imperatorin [ 53 ] and digitoxin [ 54 ] have shown significant anticancer activities in vitro and in vivo . The present study reports, for the first time, a novel NFAT1 inhibitor JapA that targets both oncogenic NFAT1 and NFAT1 interaction with the MDM2 P2 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Up to date, most of the NFAT inhibitors have been developed to nonspecifically inhibit all calcineurin-responsive NFAT isoforms no matter whether they exert their roles as an oncogene or a tumor suppressor, resulting in suboptimal efficacy against human cancer and unexpected side effects on human immune system. Several NFAT inhibitors that target either oncogenic NFAT isoforms, such as helenalin [ 51 ] and zoledronic acid [ 52 ], or NFAT-DNA binding, such as imperatorin [ 53 ] and digitoxin [ 54 ] have shown significant anticancer activities in vitro and in vivo . The present study reports, for the first time, a novel NFAT1 inhibitor JapA that targets both oncogenic NFAT1 and NFAT1 interaction with the MDM2 P2 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Certain inhibitors such as UR-1505 and digitoxin block the binding of NFAT to DNA ( 155 ). Remarkably, digitoxin specifically inhibits interaction between NFAT1 and the c- Myc promoter and thereby inhibits c-Myc-dependent transcription ( 162 ). The FOXP3-derived peptide, FOXP3 393–403, specifically inhibits FOXP3/NFAT interaction.…”
Section: Nfat Targeting Drugs For Autoimmunity: Beyond Cyclosporine Amentioning
confidence: 99%
“…Previously, a number of studies have focused on the anticancer potential of digitoxin and verified notable antitumor activities of digitoxin in lung cancer ( 17 ), pancreatic cancer ( 18 ), glioma ( 19 ), liver cancer ( 20 ), prostate cancer ( 21 ) and melanoma ( 22 ). Mechanistic studies have revealed that the growth inhibitory effect of digitoxin was associated with the induction of apoptosis ( 23 ), inhibition of epithelial-mesenchymal transition ( 21 ) and suppression of cancer cell stemness ( 24 ); however, the underlying mechanism of action of digitoxin against multidrug-resistant HCC cells has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%